Effect of ansatz on soliton propagation pattern in photorefractive crystals. Issue 1 (April 2021) - Ripai, A; Sutantyo, Trengginas E P; Abdullah, Z; Syafwan, M; Hidayat, W
Abstract: Soliton propagation and some related parameter in a photorefractive crystal are considered. This study analyzes the soliton propagation on a photorefractive crystal having both linear and quadratic electro-optical effects through a time-dependent model of nonlinear dynamics equation using the numerical split-step Fourier method. In conducting analysis, we apply various models of ansatz as initial conditions of the optical beam envelope. Based on the studies conducted, ansatz influences the soliton propagation pattern in the photorefractive crystals. Besides, we found ansatz in secant-hyperbolic and Gaussian functions as the most appropriate model for realizing solitons in crystals. Finally, the photorefractive effect supports the evolution of soliton before it achieved a level of stability.